The Effect of Ball-assisted Aerobic Training on Motor Response Speed and Passing Accuracy Under Pressure in Young Football Players - Abdullah, Yasser (Pubmedia Jurnal Pendidikan Olahraga, 2025)
This experimental study investigates the effect of ball-assistes aerobic training on reaction speed and passing accuracy under pressure among young football players. The study population was purposively selected from 145 players from youth clubs in Diyala Governorate during the 2024 sports season. The study sample consisted of 22 players from Al-Khalis Sports Club. A random draw was conducted to divide the players into two equal groups: an experimental group (11 players) and a control group (11 players). The most important issues of this study showed how ball-assisted aerobic training led to a clear improvement in reaction speed and passing accuracy under pressure among young football players. Furthermore, the most important recommendation is to regularly include ball-assisted aerobic training programs in youth training programs. With a focus on training for speed of motor response and accuracy of passing under pressure to improve technical and skillful performance in matches.